ANALISIS KESESUAIAN BUKU SISWA KELAS IV BERBASIS KURIKULUM 2013 TEMA “PAHLAWANKU” SUBTEMA “PERJUANGAN PARA PAHLAWAN” PADA PEMBELAJARAN 2 - Indriasari, Bernadine Ajeng (Program Studi Pendidikan Guru Sekolah Dasar Universitas Katolik Musi Charitas, 2018)
The purpose of this research is to know stundent book of four grade student based on Curricullum 2013 on theme “Pahlawanku”on subtheme “Perjuangan Para Pahlawan” on second learning activities with kompetensi dasar, purpose, indicator, learning activity, materials, tool and learning resources. Research method is descriptive method by analyze document is student book of four grade student based on Curricullum 2013 on theme “Pahlawanku” and teacher book of four grade student based on Curricullum 2013. The analize revolves on the rule of Menteri Pendidikan dan Kebudayaan Nasional, an article discussing about the implementation of Curricullum 2013 and article from Badan Nasional Standar Pendidikan (BSNP) website. The result of this research are found that some kompetensi dasar do not appear in indicators, purpose or learning materials,indicator is too narrow. Purpose of learning is not according with the indicators. The material in too narrow and the media is less appropriate As the conclusions, student bood of four grade student theme “Pahlawanku” needs much improved with the discrepancies in second learning activities.